RANCANG BANGUN SISTEM INFORMASI PENILAIAN KINERJA TUTOR MENGGUNAKAN METODE AHP PADA CV. INTERLEARNING CENTRE - Eva Novianti; Yahya; Yahya Ananda (Jurnal Komputer dan Sistem Informasi, 2026)
The growth of digital economic transactions in Indonesia encourages tight competition among digital wallet service providers, including the DANA application. User satisfaction is the key to maintaining relevance in the 2025 fintech market. This study aims to evaluate the influence of Content, Accuracy, Format, Ease of Use, and Timeliness variables on DANA User Satisfaction through the End-User Computing Satisfaction (EUCS) framework. The methodology used is quantitative with a sample of 111 respondents and multiple linear regression analysis. The test results show that the model has a coefficient of determination (R pangkat 2) of 51.6%. Partially, the Format variable has the most dominant positive influence. CV. Interlearning Centre is a tutoring institution that requires an objective, well-documented, and easy-to-use tutor performance assessment system for personnel staff, managers, tutors, and students. This study aims to design and develop a web-based tutor performance assessment information system using the Analytic Hierarchy Process (AHP) as the sole priority calculation method. The system development method applies the waterfall model, consisting of requirements analysis, system design, implementation, testing, and maintenance. The required data were obtained through observation of the existing process, interviews with personnel staff, and literature study. The AHP method is used to construct the decision hierarchy, develop pairwise comparison matrices, calculate criteria weights, test consistency, and generate the final tutor performance scores. The design results show that the system can manage tutor data, criteria, subcriteria, assessment periods, AHP comparisons, score inputs, and tutor ranking reports. Functional testing indicates that all main features operate according to the specified requirements. This study contributes to providing a simpler, more transparent, and measurable tutor performance assessment system model using AHP.